2018
DOI: 10.1213/ane.0000000000002708
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prehospital Tranexamic Acid on Blood Coagulation in Trauma Patients

Abstract: Early prehospital administration of TXA leads to clot stabilization and a reduction of fibrinolytic activity, causing a decrease in fibrin degradation products buildup (D-dimer).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
(46 reference statements)
0
15
0
2
Order By: Relevance
“…This is in keeping with a recent study demonstrating the benefit of on-scene administration of TXA in patients with major trauma. In this study, the normally occurring deterioration of the coagulation status between the site of injury and hospital admission was clearly mitigated by the on-scene TXA administration [504].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in keeping with a recent study demonstrating the benefit of on-scene administration of TXA in patients with major trauma. In this study, the normally occurring deterioration of the coagulation status between the site of injury and hospital admission was clearly mitigated by the on-scene TXA administration [504].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TXA should be included as part of each institutional “trauma management protocol” not the “massive blood loss” or “major haemorrhage” protocols. The benefit of on-scene TXA administration has recently been shown to be independent of the severity of injury [504].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these road safety issues, numerous changes have been made in clinical patient management. There is no doubt that more precise identification of the patient at risk for complications in the early stages after trauma is available (6)(7)(8)(9). Also, there is a higher awareness of life-threatening complications (10)(11)(12)(13), possibly related to the availability of numerous clinical parameters and biomarkers for the prediction of clinical complications (14 -17).…”
Section: Resultsmentioning
confidence: 99%
“…This is also supported in the literature, which differs in terms of its design, scope, and objectives. 20,21 The findings showed that efforts must be instigated for reducing the struggles of the medical provider. This means ensuring the presence of computed scam, blood bank, tomography scan, and more for meeting the care needs of the trauma patients.…”
Section: Discussionmentioning
confidence: 99%